Elaboração de manchas de inundação na área central de Pato Branco considerando aspectos urbanísticos - Winter, Lucas Gabriel (2018)
Flooding in urban centers occur after heavy rainfall because the storm runoff is altered due urbanization and consequent waterproofing of soils. The objective of this work is to simulate flood spots in the channeled reach of Córrego Fundo river, located in the urban area of the municipality of Pato Branco - PR, and compares them from the proposed scenarios. Two land use and occupation scenarios were analyzed, the first one being based on the 2015 satellite image of Bing Maps through Autocad Civil 3D software and the second based on a hypothetical situation, where the areas with potential for urbanization provided for in the Master Plan are fully urbanized. For the calculation of the effective precipitation, the Soil Conservation Service method was used considering the CN parameters (Curve Number) calculated for the delimited sub-basins. The transformation of effective precipitation into flow was performed through the Clark Unitary Hydrogram using the HEC-HMS software. The Intensity-Frequency-Duration equation adjusted for the municipality of Pato Branco was used to estimate the precipitation intensities for three different return periods - 25, 50 and 100 year. The temporal distribution of rainfall was performed using the Huff 1st quartile method. Model calibration and validation provided Nash-Sutcliffe efficiency indices of 0.716 and 0.652 respectively. “N” Manning value was performed for the analyzed reach with fluviometric windlass measuring. Measurement with GPS-RTK was performed to quantify the storage capacity of the retention basin upstream of the analyzed portion and to rectify a topography in the vicinity of the same The analyzed reach was modeled in Autocad Civil 3D with subsequent export to the HEC-RAS, which generated the flood maps for the different return periods. The results showed a significant increase in flooded areas from the first to the second scenario: 493.86%, 305.01% and 424.06% for the 25, 50 and 100 year return periods respectively.